Analysis of Expected Benefit in Mii Co-Creation - Radian Maulana, Dikal; Wulansari, Amilia (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Fashion industry is included in the top three industry which contribute to national domestic product (GDP) and become the highest contributor in export sector that means fashion industry have high productivity in Indonesia. Throughout the years, the way how the companies perceive their customers has changed, shifting the role of customers from passive to active in the innovation process. Consumer role during the innovation process leads to â€œco-creationâ€. Co-creation is the interactions between companies and consumers in order to co-create value. To invite customers for joining the co-creation activity, a company need to know what customers expected benefit from this activity. Mii is a fashion company that want to put co-creation with their customers in their business process as a value proposition and they need to know what is benefit expected by the customers so they can provide their expectation. This research using qualitative method with semi-structured questions to know what benefit expected by Miiâ€™s customers from co-creation activity. The result of this research is the benefit expected by Miiâ€™s customers that can be provided by Mi and put it in Miiâ€™s value proposition. From the co-creation activity Miiâ€™s customers want to learn about Indonesia culture or phenomenon, learn to make a story, make a moodbard, make product together, learn about tenun fabric, learn about fashion material, collaborate with Mii and other customers, gain network and link, showing their capabilities, and their name mention in the story of the product.Â Keywords: business process, co-creation, customer co-creation, expected benefit, value proposition